APPLYING BLENDED LEARNING IN LEARNING FOREIGN LANGUAGE AT UNIVERSITY - Akabirova Gulinodira (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to one of the topical issues of higher education, the use of a mixed form of education in the study of the discipline "Foreign language" in a technical university. Based on a theoretical analysis, the authors of the article presented their understanding of "blended learning" and its the main models that were considered in terms of the effectiveness of teaching a foreign language.